Review of the Draft National Policy on Education 2019 Chapter – 1 and Chapter 2 - Kapoor, Vandana (Voices of Teachers and Teacher Educators, 2019)
This article highlights the important recommendations laid by the draft National Education Policy, 2019 on Early Childhood Care and Education and Foundational literacy and foundational numeracy.